Pengembangan Modul Ajar Larutan Asam Basa Terintegrasi Etnokimia Berbasi Augmented Reality - Ariani, Sunniarti; Hidayanti, Ermia; Adiguna, Sya’ban Putra; Supriadi, Supriadi (Chemistry Education Practice, 2024)
The aim of this research is to develop an integrated ethnochemical acid-base solution teaching module based on augmented reality (AR) that is valid, practical and effective. The development model uses 4D design (Define, Design, Develop, Disseminate). The module that has been developed will be validated by two validators. Apart from that, effectiveness tests were also carried out through limited trials. Data collection using validation questionnaires and practicality questionnaires. Data analysis using the IBM SPSS Statistics 22 application. validation by experts and limited testing on 20 students obtained an Aiken's V value of 0.9 and an average practicality of 86%. This shows that the augmented reality (AR)-based integrated acid-base ethnochemistry teaching module that has been developed is very valid, very practical and effective for use in chemistry learning